A novel inflammatory signaling pathway in patients with slow coronary flow: NF-κB/IL-1β/nitric oxide. (July 2021) - Roshanravan, Neda; Shabestari, Alireza Namazi; Alamdari, Naimeh Mesri; Ostadrahimi, Alireza; Separham, Ahmad; Parvizi, Rezayat; Jafarabadi, Mohammad Asghari; Ghodrat, Mahshid; Akbarzadeh, Moloud; Naemi, Mohammad; Ghazi, Mahdiyeh Khabbaz Koche; Hadi, Amir; et al.
Abstract: Purpose: The slow coronary flow (SCF) was identified as delayed opacification of epicardial coronary arteries in the absence of stenotic lesion. Metabolic syndrome (MetS), oxidative stress, and inflammation may be possible known insulting factors for the pathogenesis of SCF. This investigation aimed to assess the relationship between some inflammatory markers, oxidative stress parameters and MetS components with SCF phenomenon. Methods: A total of 35 patients with SCF and 35 subjects with normal coronary flow (NCF) were included in the study. We assessed some inflammatory markers (IL-1β, IL-18, TNF-α, and NF-κB mRNA expression in peripheral blood mononuclear cells (PBMCs)). Moreover, blood samples of the participants were tested for total antioxidant capacity (TAC), glutathione peroxidase (GPX) and nitric oxide (NO) levels using enzyme-linked immunosorbent assay (ELISA). Diagnosis of MetS was based on the National Cholesterol Education Program's Adult Treatment Panel III report (ATPIII) criteria, 2005. Diagnostic criteria for coronary flow rates of all subjects were documented by thrombolysis in myocardial infarction (TIMI) frame count method. Results: SCF patients had significantly higher prevalence of MetS (46%, p = 0.048).We found that the level of TAC was significantly higher in the NCF group (p = 0.006). Furthermore, the NO concentration was significantly lower in SCF groups (p = 0.001). A significant incremental difference was detected in IL-1β (fold change 2.82 ± 0.31, p < 0.05) and NF-κB (fold change 4.62 ± 0.32, p < 0.05) mRNA expression in the SCF group when compared with its level in the NCF group. Furthermore, according to logistic regression analysis, there were significant associations between IL-1β, NF-κB expression levels and the incidence of SCF (p < 0.05). Conclusion: Based on the findings of this study, the pathogenesis of the SCF phenomenon may be closely associated with metabolic syndrome and inflammation. The NF-κB/IL-1β/nitric oxide & MetS signaling pathway might be considered as potential therapeutic targets in the management of SCF patients but further researches is required to guarantee these findings.